TERAPI BIRTH BALL UNTUK MENURUNKAN INTENSITAS NYERI PERSALINAN - Debora Paninsari (Universitas Prima Indonesia, 2021)
Pain in childbirth has the highest degree of pain among other pain, so that many women are not ready to have children because they imagine the pain that will be presented at the time of labor later. The general objective of this study was to determine whether there was an effect of birth ball therapy on pain intensity in labor. Univariate and bivariate analysis using Wilcoxon test analysis. Bivariate analysis is used to see the effect of the independent variable (independent) on the dependent variable using the Wilxocon test analysis. Of the 50 respondent mothers who carried out the variable therapy pre-test birth ball who were very painful and 29 respondents had pain (58%), and a minority of respondents had little pain, 21 people (42%). And on the post-test respondents the least pain was increased by 32 respondents (64%), while the minority of pain was quite severe as many as 18 respondents (36%). A significant effect on the effect of birth ball therapy on labor pain where the p value is 0.00 <0.05. The results are expected to have an effect on birth therapy on labor pain. The results of the Wilcoxon test analysis with a degree of significance (α) = 0.05 and a P value of 0.00 were obtained (α<0.05) which can be seen from the value which means that Ho is rejected and Ha is accepted. The conclusion is that there is an effect of birth ball therapy on labor pain.